A phase II, multicenter trial of rindopepimut (CDX-110) in newly diagnosed glioblastoma: the ACT III study. Issue 6 (13th January 2015) - Schuster, James; Lai, Rose K.; Recht, Lawrence D.; Reardon, David A.; Paleologos, Nina A.; Groves, Morris D.; Mrugala, Maciej M.; Jensen, Randy; Baehring, Joachim M.; Sloan, Andrew; Archer, Gary E.; Bigner, Darell D.; et al.
Abstract: Background: The epidermal growth factor receptor variant III deletion mutation, EGFRvIII, is expressed in ∼30% of primary glioblastoma and linked to poor long-term survival. Rindopepimut consists of the unique EGFRvIII peptide sequence conjugated to keyhole limpet hemocyanin. In previous phase II trials (ACTIVATE/ACT II), rindopepimut was well tolerated with robust EGFRvIII-specific immune responses and promising progression-free and overall survival. This multicenter, single-arm phase II clinical trial (ACT III) was performed to confirm these results. Methods: Rindopepimut and standard adjuvant temozolomide chemotherapy were administered to 65 patients with newly diagnosed EGFRvIII-expressing (EGFRvIII+) glioblastoma after gross total resection and chemoradiation. Results: Progression-free survival at 5.5 months (∼8.5 mo from diagnosis) was 66%. Relative to study entry, median overall survival was 21.8 months, and 36-month overall survival was 26%. Extended rindopepimut vaccination (up to 3.5+ years) was well tolerated. Grades 1–2 injection site reactions were frequent. Anti-EGFRvIII antibody titers increased ≥4-fold in 85% of patients, and increased with duration of treatment. EGFRvIII was eliminated in 4/6 (67%) tumor samples obtained after >3 months of therapy. Conclusions: This study confirms, in a multicenter setting, the preliminary results seen in previous phase II trials of rindopepimut. A pivotal, double-blind, randomized, phase III trial ("ACT IV") is under way.